Mastering Microsoft Lync Server 2013 - Hanna, Keith (Wiley, 2013)
Everything you need to know to get Lync 2013 up and running smoothly As a Unified Communications (UC) technology, Lync allows you to keep track of your contacts' availability so you can communicate with anyone, anywhere, and at any time. With this hands-on book, you will learn how to administer the newest and most robust version of Lync Server in order to send an IM; start or join an audio, video, or web conference; or make a phone call through a familiar interface. Packed with real-world exercises throughout, this unique resource encourages you to learn from the best practices an.